The Biblical world - Harper, William Rainey, 1856-1906; Burton, Ernest De Witt, 1856-1925; Mathews, Shailer, 1863-1941
"Books for New Testament study ... [By] Clyde Weber Votaw" v. 26, p. 271-320; v. 37, p. 289-352.